2018
DOI: 10.1155/2018/3425615
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Polysaccharide from Spirulina and Evaluation of Its Activities

Abstract: Background Polysaccharide of Spirulina platensis (PSP) is a kind of water-soluble polysaccharide extracted from Spirulina platensis. It has been proved to have antitumor, antioxidation, antiaging, and antivirus properties. And it has a promising prospect for wide application. Objective This study aims to identify an extraction process for high-purity polysaccharide in Spirulina (PSP) through a series of optimization methods and then evaluates its initial antiaging activities. Methods Four kinds of extraction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 18 publications
1
35
2
Order By: Relevance
“…Moreover, increasing temperature increases the solubility due to the weakening of the bonds between the carbohydrate and the matrix (Ho, Cacace, & Mazza, 2007; Piñeiro, Palma, & Barroso, 2004). Polysaccharides from plant sources (mainly acidic) are highly soluble in alkaline solutions with increasing temperature that are favorable for breaking cell walls and releasing polysaccharide gums to achieve higher extraction yield (Wang et al., 2018). However, there was a slight decrease in yield (6.74%) when temperature was further increased to 100 °C that may occur due to the degradation of compounds at higher temperature (Ho et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, increasing temperature increases the solubility due to the weakening of the bonds between the carbohydrate and the matrix (Ho, Cacace, & Mazza, 2007; Piñeiro, Palma, & Barroso, 2004). Polysaccharides from plant sources (mainly acidic) are highly soluble in alkaline solutions with increasing temperature that are favorable for breaking cell walls and releasing polysaccharide gums to achieve higher extraction yield (Wang et al., 2018). However, there was a slight decrease in yield (6.74%) when temperature was further increased to 100 °C that may occur due to the degradation of compounds at higher temperature (Ho et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other flocculation methods, ZTC1 + 1 resulted in not only the highest polysaccharide purity, but also the least polysaccharide loss. The polysaccharide purity after ZTC1 + 1 treatment (> 80%) was even 22% higher than that with enzymatic trichloroacetic acid (TCA) method where 3% papain and 5% TCA were sequentially used to remove impurities in the crude polysaccharide extracts from A. platensis [24]. Compared with traditional deproteinization methods such as Sevage and TCA method where organic reagents and complicated purification process are often involved (e.g., 5–10 times repeated treatments in Sevage method) [23], ZTC1 + 1 is an effective, simple and environmental-friendly way for polysaccharide purification as an impurity scavenger from algae and other natural products.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Wu et al [23] and Wang et al [25] also reported that glucose was the main component (> 90%) of the polysaccharides from A. platensis (Table 4). However, considerable amounts of other studies revealed that instead of Glc, Rha accounted for the main sugar moiety of the polysaccharides from A. platensis (Table 4), with the proportion of which reaching up to approximately 50% [24, 4547]. Additionally, Chen et al [20] found that A. platensis water-soluble polysaccharides were composed of 57.5% Man and 42.5% Glc, which was quite different from the results discussed above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since spirulina is rich in amino acids (AAs), fatty acids (FAs), docosahexaenoic acid, vitamins and diverse minerals, spirulina has been considered as “the most ideal food in the 21st century” by the World Health Organization, and the Food and Agriculture Organization of the United Nations (Batista, Gouveia, Bandarra, Franco, & Raymundo, ; Gupta, Aglave, & Lokhande, ). Meanwhile, spirulina also contains various bioactive components, such as polysaccharide, cyanobacteria protein, beta carotene, linoleic acid and γ‐linolenic acid, exhibiting the characteristics of antibacterial, anti‐oxidation, antivirus and immunity enhancement (BingyueWang et al, ; Muthusamy, Thangasamy, Raja, Chinnappan, & Kandasamy, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%